Social media and morality : losing our self control / Lisa S. Nelson, University of Pittsburgh. - Nelson, Lisa S., 1963- (Cambridge University Press, 2018)
Is social media changing who we are? We assume social media is only a tool for our modern day communications and interactions, but is it quietly changing our identities and how we see the world and one another? Our current debate about the human behaviors behind social media misses the important effects these social networking technologies are having on our sense of shared morality and rationality. There has been much concern about the loss of privacy and anonymity in the Information Age, but little attention has been paid to the consequences and effects of social media and the behavior they engender on the Internet. In order to understand how social media influences our morality, Lisa S. Nelson suggests a new methodological approach to social media and its effect on society. Instead of beginning with the assumption that we control our use of social media, this book considers how the phenomenological effects of social media influences our actions, decisions, and, ultimately, who we are and who we become. This important study will inform a new direction in policy and legal regulation for these increasingly important technologies.